PROJECT "IVOŠ - INCREASE QUALITY LEVEL IN EDUCATION WITH INTRODUCE INTERACTIVE TEACHING TO SCHOOLS" - Milan, KLEMENT; LAVRINČÍK, Jan (Trends in education, 2009)
The article present project "IVOŠ - increase quality level in education with introduce interactive teaching to schools (CZ.1.07/1.1.04/01.0154) ". This project is cofinanced by the European social fund EU and the state budget of the Czech Republic.
Keywords: interactive white-board; interactive lesson; modernisation.